“RAMAYANA THEMES DEPICTED IN THE TEMPLE ART OF ANDHRADESA” – A SPECIAL REFERENCE TO RAYALASEEMA - Govindu, Surendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The worship of Sri Rama is as ancient as temple worship in this land. The great Itihasa Ramayana by saint Valmiki itself has the sanctity of scripture to the Hindus. In India, there are thousands of temples dedicated to Lord Sri Rama, from Ayodhya, his birthplace in Uttar Pradesh, down to Rameswaram at the southernmost tip of the country. Temples of the Andhra Pradesh are treasure houses of sculptures and art forms representations of gods and goddesses and episodes from their mythologies. The Ramayana cult images found in the different dynasty’s temples in the Andhradesa may be divided into Sculpture, Idol of Sri Rama and Sita, Sculpture and Paintings in Ramayana themes. Andhra Pradesh has a unique place not only in Indian History, but geographically located midway in subcontinent to receive the cultural impacts from the north and pass them on to Southern India. It has many ancient centers of art and culture. Some of them are indigenous in character. In this research paper discussed the cult of Sri Rama iconographic features of sculptures and images of Ramayana themes in important Vaishnava temples in Andhra Pradesh a special reference to Rayalaseema region.